An Oxygen‐Insensitive Degradable Resist for Fabricating Metallic Patterns on Highly Curved Surfaces by UV‐Nanoimprint Lithography. Issue 19 (3rd September 2014) - Hu, Xin; Huang, Shisong; Gu, Ronghua; Yuan, Changsheng; Ge, Haixiong; Chen, Yanfeng
<x xml:space="preserve">Abstract</x> In this paper, an oxygen‐insensitive degradable resist for UV‐nanoimprint is designed, comprising a polycyclic degradable acrylate monomer, 2, 10‐diacryloyloxymethyl‐1, 4, 9, 12‐tetraoxaspiro [4.2.4.2] tetradecane (DAMTT), and a multifunctional thiol monomer pentaerythritol tetra(3‐mercaptopropionate) (PETMP). The resist can be quickly UV‐cured in the air atmosphere and achieve a high monomer conversion of over 98%, which greatly reduce the adhesion force between the resist and the soft mold. High conversion, in company with an adequate Young's modulus (about 1 GPa) and an extremely low shrinkage (1.34%), promises high nanoimprint resolution of sub‐50 nm. The cross‐linked resist is able to break into linear molecules in a hot acid solvent. As a result, metallic patterns are fabricated on highly curved surfaces via the lift off process without the assistance of a thermoplastic polymer layer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>